1135. Strongyloides Stercolaris Serology in Transplant Patients: To Test or Not?. (26th November 2018) - Rivera, Karla Rivera; Shah, Tulsi; Garcia-Diaz, Julia; Hand, Jonathan
Abstract: Background: Strongyloides stercoralis is an intestinal nematode endemic to the tropics, subtropics, and to a limited extent the United States and Europe. The global estimates of strongyloidiasis are reported to range from 3 to 100 million infected worldwide; however, the true US prevalence is unclear. The seroprevalence of infection in solid-organ transplant candidates and recipients in the New Orleans, Louisiana region is also unknown. The purpose of this study was to identify the prevalence of Strongyloides seropositivity within transplant candidates at Ochsner Medical Center (OMC). Methods: Patients were identified using EPIC-CLARITY with ICD-9 and ICD-10 codes for any solid-organ transplant at OMC from July 2012 to December 2016. Inclusion criteria were age 18 or older, patients evaluated for solid-organ transplant, and Strongyloides IgG testing. Patients were excluded if they had other immunocompromising conditions or exposures including but not limited to steroids, TNF-alpha, or biologic agent use. The primary outcome was the overall prevalence rate of strongyloidiasis at OMC. Secondary outcome was the comparison of prevalence between January 1, 2012 to July 31, 2016 (when testing was ordered based on risk stratification) vs. August 1, 2016 to December 31, 2016 (when routine testing was implemented). Results: We analyzed a total of 1, 047 patients which had 1, 128 tests ordered for S trongyloides . Of those, 985 were unique patients (62 patients had multiple serological tests resulting in 81 repeat tests). During July 1, 2012 to July 31, 2016 testing yielded a total of 822 tests. From August 1, 2016 to December 31, 2016 testing yielded 306 tests. Overall, 43/1, 128 (3.8%) tests were positive for Strongyloides . The remaining 1, 085/1, 128 (96.2%) tested negative. For our secondary outcome, we found that testing based on risk stratification yielded 22/822 (2.7%) positives while testing for all patients we had 21/306 (6.9%) positives. Conclusion: Our data suggest that testing based on risk stratification yielded a lower prevalence rate as compared with generalized testing, underestimating the true incidence of disease (2.7% vs. 6.9%). Testing all patients being evaluated for transplantation will capture a greater number of patients with positive serology. Disclosures: J. Garcia-Diaz, Astellas Pharma: Speaker's Bureau, Speaker honorarium.